The origins of the “Leões” flour and pasta factory. The present of the Arts and Architecture School of the University of Évora (Portugal). - Matos, Ana Cardoso de (2020)
The Leões flour and pasta factory, which was one of the most important factories of the Alentejo, is a typical example of the European milling factories which emerged in 19th-century Europe. It was one of the 31 modern factories built in the districts of Beja, Évora and Portalegre between the late 19th century and the 1930s. It was established in 1916 in Évora. In 1993, the factory’s lack of competitiveness led to its closure and, after a few years of neglect, in 1998, the University of Évora, following the example of other universities, acquired the building so it would accommodate the Arts and Architecture School. The search of the origins of the factory was one of the main objectives of the researchers who were working about this field. However, it was not available the original process of the industry which would help to examine this study case completely, still now. In this paper we intend to analyse firstly, the origins of the Leões factory and its technical and architectural characteristics, and secondly, the renovation of the building as the Arts and Architecture School of the University of Évora.